Urbanization without structural transformation in Lagos, Nigeria - Abiodun Oluwole Folawewo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study examines the relationship between urbanization and structural transformation in Lagos. Specifically, the study focuses on spatial distribution of economic activities, and the patterns and drivers of, as well as constraints to, structural transformation in the city of Lagos from a political settlement perspective. Both quantitative and qualitative analytical techniques are applied to data derived from primary and secondary sources. Findings show a significant variation in spatial distribution of business establishments in Lagos, with dominance of the services sector in terms of share of establishments and employment. This is reflected with varying degree in the large informal employment across the city. Although there is a shift from agriculture, there is little or no structural transformation as the movement is largely into the lowproductive services sector with moderate movement into manufacturing. The dominance of services establishment and employment shares suggests that even though Lagos has booming economic activities, these activities are low-income generating with low capacity for labour employment and productivity growth. It is also found that the 'narrow-concentrated' pattern of political settlement of the city coupled with other factors have effects on economic activities and structural transformation in the city.
Keywords: O11; R10; R11; 330; employment; productivity; urbanization; structural transformation; Lagos